Study of Serum FT3, FT4 and TSH Levels in Pregnant Women - Yeasmin, Shahanara; Hossain, AFM Anwar; Yeasmin, Tahmina; Amin, Md Ruhul (Medicine Today, 2016)
Thyroid disease have a strong predominance in woman of childbearing age. Pregnancy may be associated with thyroid dysfunction. Our objective was to assess the serum FT3, FT4 and TSH levels in pregnant women. This cross-sectional analytical study was done in the Department of Physiology of Dhaka Medical College from July 2006- June 2007. Total 50 apparently healthy women of low socioeconomic class, age ranged from 18- 40 years were selected from the Outpatient Department of urban primary health care project at Mirpur, Dhaka. Out of them 30 pregnant women of different trimester were taken as study group and 20 age matched non pregnant women were taken as control. Serum FT3, FT4 and TSH levels were parameters in both groups. Statistical analysis was done by the SPSS 12.0 programme. The means ( SD) of serum FT3 levels were 6.36 1.16 p mol/L and 6.38 1.38 p mol/L, FT4 levels were 20.25 4.77 pmol/L and 19.39 8.17 pmol/L and TSH levels were 0.96 0.96 mIu/L and 1.27 0.86 mIu/L in group A (Study) and group B (control) respectively. The difference of means ( SD) of serum FT3 , FT4 and TSH levels were not significant (p>0.05) between group A and B. From the statistical analysis of the results obtained in the present study and their comparison with those of published reports, it may be concluded that there is no change of serum FT3, FT4 and TSH levels in pregnancy. Medicine Today 2015 Vol.27(2): 1-4